SIMULATION OF AN AXIAL FLOW TURBINE RUNNER’S BLADES USING CFD - Khalifa, Diaelhag (European Scientific Journal, ESJ, 2013)
This study aims to use computational fluid dynamics software package (CFX) to study and analyze flow’s behavior in an axial flow turbine. This turbine used in low head and high flow rate hydropower plant. This study indicates that, performance of the designed blades is acceptable. These blades can be used in Kaplan turbine to produce a power with some addition design modification. These modifications can be made to reduce the tailing edge vortices (in suction side) of the blade and boundary layer forming in the leading edge of the blade. Also these modifications need furtherer analysis and more testing using another commercial CFD codes to investigate the results. Also this study focused to found the variations of velocity components and the pressure by average circumferential area (ACA) from inlet to outlet of the blades and used as factors to analyzed the flow inside the blades, the results of this analysis shows a good prediction of the flow behavior inside the blades and this lead to acceptable blade design, which can be used in Kaplan turbine.